Prioritizing factors in social media crisis communication for resilience enhancement using analytical hierarchy process - Mundottukandi, Mohammed S.; Jusoh, Yusmadi Yah; Pa, Noraini Che; Haizan Nor, Rozi Nor; Bukar, Umar Ali (Institute of Electrical and Electronics Engineers, 2024)
In today's era dominated by social media, crisis communication has become increasingly complex in the evolving landscape of crisis management, shaped by globalization and technological advancements. The pivotal role of social media in facilitating information seeking and sharing during crises underscores the need to identify factors that enhance resilience in crisis communication. As a result, the study presented herein delves into the intricate interplay between information-seeking, information-sharing, and social media usage factors, examining their influence on resilience within the context of crisis management. Utilizing the Analytical Hierarchy Process (AHP), the research creates a comprehensive hierarchical model of these factors and elucidates their priorities through expert pair-wise comparisons. The results reveal that information-seeking factors dominate the ranking, highlighting the paramount importance of understanding how individuals seek and engage with information during crises. Specifically, the findings suggest that factors such as media choice, crisis type, and trust play pivotal roles in resilience building during crisis situations. In the realm of information sharing, the study underscores the significance of factors like sentiment, authority, and relevance in shaping the resonance and effectiveness of shared content. Moreover, the analysis unveils the outcomes of social media usage factors, spotlighting elements such as media exposure, uncertainty, and involvement, and showcasing their role in driving individuals' engagement with crisis-related content on social platforms. By leveraging the AHP methodology, this research unravels the priorities of factors that underpin the efficacy of Social Media Crisis Communication (SMCC). Accordingly, it underscores the potential of AHP as an invaluable tool for navigating the intricate landscape of SMCC literature, offering fresh perspectives and empirical insights. Embracing the prioritized factors unveiled in this analysis, crisis managers and communicators can tailor their strategies to better align with the dynamics of social media and enhance resilience-building efforts in an ever-evolving crisis landscape. © 2013 IEEE.